Times Square red, Times Square blue - Delany, Samuel R. (Sexual cultures, 2001)
Times Square Red, Times Square Blue paints a portrait of a society dismantling the institutions that promote communication between classes, and disguising its fears of cross-class contact as "family values." Unless we overcome our fears and claim our "community of contact," it is a picture that will be replayed in cities across America.